Does Straw Returning Amended with Straw Decomposing Microorganism Inoculants Increase the Soil Major Nutrients in China’s Farmlands? - Zhifeng He; Xinrun Yang; Jing Xiang; Zelu Wu; Xinyi Shi; Ying Gui; Manqiang Liu; Yusef Kianpoor Kalkhajeh; Hongjian Gao; Chao Ma (Agronomy, 2022)
Although straw-decomposing microbial inoculants (SDMI) are capable to generally promote the fertility of straw-amended soils, their impact on the release of individual soil major nutrients remains controversial. Additionally, the combined effects of SDMI and environment/management on various forms of nutrients remain poorly documented. To fill these research gaps, we conducted a meta-analysis study using 1214 paired observations from 132 field trials in China. Our results showed that SDMI significantly increases the total and available concentrations of nitrogen, phosphorus, and potassium in soil (p < 0.05), although increases in nutrients varied with different conditions. Moreover, mean annual precipitation (MAP) had significant correlations with the effects of SDMI-amended straw on soil total nitrogen (p = 0.008) and available nitrogen (p = 0.0006). The effect of SDMI-amended straw on soil total phosphorus and soil available potassium was mainly correlated with soil organic matter (p = 0.032) and MAP (p = 0.049), respectively. Our findings indicate that SDMI-amended straw can have a measurable impact on the status of soil major nutrients. In particular, the application of SDMI-amended rice straw with an initial C/N ratio of ≤15 to neutral soils in temperate and subtropical monsoon climates is a promising strategy.